Effect of Annealing on the Magnetic Properties of FeCoNiCuNbSiB Soft Magnetic Alloys - Li, Z.; Yao, K. F.; Liu, T. C.; Li, X.; Wang, S. (Frontiers in Materials, 2022)
A series of nanocrystalline soft magnetic alloys with nominal composition of Fe66.8-xCo10NixCu0.8Nb2.9Si11.5B8 (x=1-15 at. %) were developed and studied. Effect of annealing on the soft-magnetic properties, crystallization behavior and domain structure were investigated. The alloys with higher Ni content were prone to exhibit stronger magnetic anisotropy. The Fe66.8Co10Ni10Cu0.8Nb2.9Si11.5B8 alloy exhibited excellent soft-magnetic properties, including the low permeability of 2000, low coercivity of about 0.6 A/m and low remanence of 2.4 mT, together with a temperature gap of 128K between two crystallization onset temperatures. It has been found that the Ni content and the annealing process possess significant effects on the soft magnetic property of the nanocrystalline alloys. It shows the developed Fe66.8Co10Ni10Cu0.8Nb2.9Si11.5B8 nanocrystalline alloy exhibits great potentials for applying in the field of common mode chokes or current transformers, due to its ability to resist the direct current.